2014
DOI: 10.1007/s00436-014-4228-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel CDPK1 inhibitor—a potential treatment for cryptosporidiosis in calves?

Abstract: Cryptosporidium parvum is a zoonotic agent that infects humans and animals occasionally causing severe, watery diarrhoea. In immunocompetent hosts, cryptosporidiosis is self-limiting but can have a fatal outcome in immunocompromised individuals. Cryptosporidium is one of the most common causes of waterborne diseases (recreational water and drinking water) in humans, a leading cause of moderate to severe childhood diarrhoea, and a major agent of diarrhoea in calves leading to high economic losses and up to 10% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…While treated calves had better clinical health scores, firmer stools, and a 94% reduction in oocyst shedding as compared to controls, no significant reduction in diarrhea was observed, based on fecal volumes. Lendner et al also reported a good parasitological outcome in calves treated with BKI-1294 at 10 mg/kg every other day, but calves in that preliminary report developed few clinical symptoms to evaluate conclusively [24]. Subsequent pharmacokinetic data from calves in the present report indicate that the allometrically determined dosage we (and Lendner et al [24]) used was suboptimal, with stool and plasma BKI levels that were essentially zero on the second day after each dosing.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…While treated calves had better clinical health scores, firmer stools, and a 94% reduction in oocyst shedding as compared to controls, no significant reduction in diarrhea was observed, based on fecal volumes. Lendner et al also reported a good parasitological outcome in calves treated with BKI-1294 at 10 mg/kg every other day, but calves in that preliminary report developed few clinical symptoms to evaluate conclusively [24]. Subsequent pharmacokinetic data from calves in the present report indicate that the allometrically determined dosage we (and Lendner et al [24]) used was suboptimal, with stool and plasma BKI levels that were essentially zero on the second day after each dosing.…”
Section: Discussionmentioning
confidence: 52%
“…Lendner et al also reported a good parasitological outcome in calves treated with BKI-1294 at 10 mg/kg every other day, but calves in that preliminary report developed few clinical symptoms to evaluate conclusively [24]. Subsequent pharmacokinetic data from calves in the present report indicate that the allometrically determined dosage we (and Lendner et al [24]) used was suboptimal, with stool and plasma BKI levels that were essentially zero on the second day after each dosing. Given these pharmacokinetics data and considering the accelerated gastrointestinal transit time resulting from diarrhea, we hypothesized that more-frequent dosing would result in better treatment outcomes.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…In turn, chronic infection is characterized by the formation of intracellular tissue cysts in brain and muscular tissues that harbor slowly proliferating bradyzoites. Calcium-dependent protein kinases (CDPKs), encoded by apicoplast-associated genes and, thus, only found in apicomplexan parasites and plants, represent excellent drug targets in several apicomplexans such as Plasmodium falciparum (6), Cryptosporidium parvum (7,8) where novel drug targets are of crucial interest (9), N. caninum (10), Eimeria tenella, and Babesia bovis (11). Excellent correlations between cell activity and CDPK1 inhibition were achieved by compounds from a focused bumped kinase inhibitor (BKI) library.…”
mentioning
confidence: 99%